2008
DOI: 10.1093/ajcn/87.5.1212
|View full text |Cite
|
Sign up to set email alerts
|

Relation of central adiposity and body mass index to the development of diabetes in the Diabetes Prevention Program

Abstract: In the placebo and lifestyle groups, VAT at both cuts, WHR, and WC predicted diabetes. No measure predicted diabetes in the metformin group. CT provided no important advantage over these simple measures. SAT did not predict diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
187
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(202 citation statements)
references
References 39 publications
9
187
0
6
Order By: Relevance
“…Studies carried out in different ethnicities showed that VAT, but not SAT, was strongly associated with the development of diabetes 16,17 and coronary heart disease. 18 Increased VAT was associated with impaired glucose tolerance 19 or insulin resistance.…”
Section: Discussionmentioning
confidence: 98%
“…Studies carried out in different ethnicities showed that VAT, but not SAT, was strongly associated with the development of diabetes 16,17 and coronary heart disease. 18 Increased VAT was associated with impaired glucose tolerance 19 or insulin resistance.…”
Section: Discussionmentioning
confidence: 98%
“…3. Subcutaneous adipose tissue can be reliably measured by CT scan at the L2-L3 and L4-L5 disc spaces [25].…”
Section: Ligaments Thickness Estimationmentioning
confidence: 99%
“…Quantifying the adjustment of haptic feedback according to BMI can provide simulation of obese patients which are considered to be difficult. The size and shape of ligaments and vertebrae and the force required for the needle to traverse each tissue layer changes according to patient body shape [25].…”
Section: Body Shape Visualisation Using Mesh Deformationmentioning
confidence: 99%
“…If less radiation exposure is desired, a measurement can be made in L1-L4 single scanning region. Visceral adipose tissue and subcutaneous adipose tissue can be measured at the L2-L3 and L4-L5 disc spaces [27].…”
Section: Ctmentioning
confidence: 99%